(untitled) (International Journal of Communication Systems and Network Technologies, 2021)
The tiles industries are growing in the Indian market, where consumers are always moving and they are not satisfied with the same product. The company’s Hercules job is to retain customers. Therefore, they place a high priority on customer satisfaction. The study is about customer satisfaction towards Kajaria Products. The theme of selected tiles deals with various factors and relationships that directly affect customer satisfaction in Kajaria products. Kajaria is a survey for customer satisfaction. Selected descriptions in this article describe the various factors and relationships that directly affect customer satisfaction with Kajaria products. we can see intense competition in all industries from pins to platforms. Customers’ tastes and preferences are very dynamic and can change whenever they want, and they are constantly on the lookout for the best and latest products and services. Retaining customers is a difficult task. Therefore, effective customer satisfaction data are needed.